Development of Web-Based Learning Media Using Google Sites in Vocational High School Informatics Subjects - Rudi Yanto; Waskito Waskito; Hansi Effendi; Wawab Purwanto (Journal of Vocational Education Studies, 2023)
This study aims to create web-based instructional media with Google Sites and then assess the media's validity, practicability, and efficacy. This research used the R & D (Research and Development) technique with the 4-D development model (Four-D Model). Data collection used 3 types of questionnaires consisting of media, material, and language validation questionnaires. To test the effectiveness of the media, pretest and posttest questions were used, which had gone through a process of validation, reliability, discriminatory power and level of difficulty. The test results of all validations show that an average validity index of 0,919 in the Very Eligible criteria. Media practicality is in the Very Practical category, with an average practicality percentage of 84.91% across instructors and students. The media's effectiveness level is Effective Enough, with an average N-Gain score of 60.77% and a substantial T-Test value of 0.000, indicating that it may be utilized effectively in SMK Informatics learning. This study conducted trials on students who had just implemented the Merdeka curriculum.